Laparoscopic skills acquisition: a study of simulation and traditional training. Issue 12 (19th June 2013) - Marlow, Nicholas; Altree, Meryl; Babidge, Wendy; Field, John; Hewett, Peter; Maddern, Guy J.
Abstract Background Training in basic laparoscopic skills can be undertaken using traditional methods, where trainees are educated by experienced surgeons through a process of graduated responsibility or by simulation‐based training. This study aimed to assess whether simulation trained individuals reach the same level of proficiency in basic laparoscopic skills as traditional trained participants when assessed in a simulated environment. Methods A prospective study was undertaken. Participants were allocated to one of two cohorts according to surgical experience. Participants from the inexperienced cohort were randomized to receive training in basic laparoscopic skills on either a box trainer or a virtual reality simulator. They were then assessed on the simulator on which they did not receive training. Participants from the experienced cohort, considered to have received traditional training in basic laparoscopic skills, did not receive simulation training and were randomized to either the box trainer or virtual reality simulator for skills assessment. The assessment scores from different cohorts on either simulator were then compared. Results A total of 138 participants completed the assessment session, 101 in the inexperienced simulation‐trained cohort and 37 on the experienced traditionally trained cohort. There was no statistically significant difference between the training outcomes of simulation and traditionally trained participants, irrespective of the simulator type used. Conclusions The results demonstrated that participants trained on either a box trainer or virtual reality simulator achieved a level of basic laparoscopic skills assessed in a simulated environment that was not significantly different from participants who had been traditionally trained in basic laparoscopic skills.